Embracement with risk classification: relationship of justice with the user - Andrea Stella Barbosa Lacerda; Marta Sauthier; Graciele Oroski Paes; Enéas Rangel Teixeira (Associação Brasileira de Enfermagem, 2019)
ABSTRACT Objective: to describe the conception of justice of nurses and users regarding the Risk Classification in Emergency Unit; to analyze the conception of justice in the implementation of the Risk Classification in Emergency Unit from the user's recognition; to discuss, from Axel Honneth's Theory of Recognition, justice with the user in the Risk Classification in Emergency Unit. Method: qualitative research of descriptive, exploratory typology, which used action research as a method. Bardin's Content Analysis was carried out. Results: a category was created: "Justice versus Injustice" and three subcategories: "Autonomy/Freedom versus Heteronomy/Subordination"; "Communication versus Hermeneutic Problems"; "Contributions versus Conflicts". Final considerations: Embracement with Risk Classification presents difficulties in its interpretation and effectiveness; there are situations of disrespect that compete against the required ethics. Justice addressed by this study will be achieved by an emergency access system that meets user expectations, recognizing it as a subject of rights.